Is the risk of tenofovir-induced nephrotoxicity similar in treatment-naïve compared to treatment-experienced patients? - Low, Joo Zheng; Khoo, Su Pei; Nor Azmi, Nuruljannah; Chong, Meng Li; Sulaiman, Helmi; Azwa, Iskandar; Tan, Ching Hooi; Kamarulzaman, Adeeba; Rajasuriar, Reena (Wiley, 2018)
Background: Tenofovir disoproxil fumarate (TDF) is the recommended first-line nucleoside reverse transcriptase inhibitor (NRTI) in the management of human immunodeficiency virus (HIV); however, its use is associated with nephrotoxicity. Aim: To assess if the risks of renal impairment were similar in treatment-naïve compared to treatment-experienced patients initiating tenofovir given their different background clinical characteristics. Method: This was a retrospective observational study conducted at the University Malaya Medical Centre, Malaysia and included all HIV-infected adults who received tenofovir for at least 3 months and had an estimated glomerular filtration rate (eGFR) >60 mL/min at tenofovir initiation. The incidence of renal impairment was defined as a 25% decrease in eGFR from baseline or the development of chronic kidney disease. Clinical and demographic characteristics were extracted from medical records. Risk factors associated with tenofovir-induced renal impairment were determined using multivariate logistic regression. Results: This study included 314 patients and almost half of them (49%) were treatment-naïve at tenofovir initiation. The majority of patients were male (89.5%) with a median (interquartile range) baseline creatinine clearance of 99.1 mL/min (85.0–114.0). Thirty (9.4%) patients developed tenofovir-induced renal impairment and the incidence rate was higher in treatment-experienced versus treatment-naïve patients (7.0 vs 3.3 cases/100 person-years, p = 0.049). Risk factors associated with tenofovir-induced nephrotoxicity in multivariate analysis were older age (p = 0.001), anaemia (p = 0.027), concurrent hypertension (p = 0.014) and higher baseline eGFR (p = 0.007). Conclusion: Treatment experience was not an independent risk factor but was rather confounded by multiple characteristics associated with an increased risk of TDF-induced nephrotoxicity. Monitoring all patients presenting with these risks regardless of treatment experience is crucial.